Proper Acknowledgment? - East, J. (Journal of University Teaching and Learning Practice, 2005)
The concern in Australian universities about the prevalence of plagiarism has led to the development of policies about academic integrity and in turn focused attention on the need to inform students about how to avoid plagiarism and how to properly acknowledge. Teaching students how to avoid plagiarism can appear to be straightforward if based on the notion that plagiarism is copying without proper acknowledgment. This paper reviews the term ‘proper acknowledgment’ in the academic context and argues that proper acknowledgement can be a matter of context and perception. In this paper forms of plagiarism are reviewed, reasons for student plagiarism are considered and different contexts for acknowledgement and how these fit in with concepts of attribution and originality are discussed. Comments from international students new to Australian academic culture provide insights and reveal that students in trying to master the rules of acknowledgment can be perplexed and concerned about when and why they should acknowledge.